Analisis Perilaku Pedagang Pasar Pagu Ditinjau dari Etika Bisnis Islam - Nurrokhim, Isma; Suherlina, Etik; Maghfirah, Izzatun; Khamidah, Yuni Astriana (Universitas Islam Raden Rahmat, 2025)
Trading behaviour in muamalah plays an important role in people's lives in transactions between each other to fulfil daily living needs. This research includes research that uses a qualitative approach, namely in the form of a research procedure that produces descriptive data or in the form of written speech and behaviour that can be observed from the subject himself. The results of this research show that the behaviour of Pagu Market traders in Kediri Regency is partly in accordance with procedures that are in accordance with Islamic teachings, namely prioritizing honesty, showing good behaviour and being careful in carrying out their trading routines. However, there are also things that are not in accordance with Islamic teachings, namely the behaviour of traders who praise the quality of goods unreasonably, the unfriendliness of traders, the dishonesty of traders, and the injustice of traders towards buyers. The trading behaviour of traders in the market is relatively balanced between that which is in accordance with Islamic teachings and trading behaviour that is not yet appropriate.